Capital in the Twenty-First Century by Thomas Piketty - Estrada, Fernando (2021)
What we find here is a historiographical exercise compared like Tocqueville efforts by the mid-nineteenth century to understand the effects of the French Revolution. Piketty discovers that long periods of time analyzing the wealth derived capital has unprecedented dimensions. From his historical research in notary archives Piketty could see better multiple parallels also-and differences between the current ownership structure, or what he calls La Belle Epoque and this shared by the companies in early twenty-first century phenomenon. The collection of materials and overall project outcomes are in the database: World Top Incomes Database, available historical data and technical information for a thorough reading of the results